KEARIFAN LOKAL MASYARAKAT DALAM KEGIATAN LADANG BERPINDAH DI DUSUN LAEK DESA BENGKILU KECAMATAN TUJUH BELAS KABUPATEN BENGKAYANG - Silvi, .; Lumangkun, Agustine; Wardenaar, Evy (JURNAL HUTAN LESTARI, 2017)
Shifting cultivation is a form of traditional farming system that became the custom, tradition and culture of the farmers in West Kalimantan. The equipment used for this activity relies on axes and machetes. The area to be slashed and burned is two hectars in average per family of land forest. The purposes in this research are to know 1) The form of social network structures in individual level of shifting cultivators in maintaining the value of the local wisdom seen form the centrality within network. 2) the forms of local wisdom of the community in shifting cultivation. The research took place in Laek Sub-Village of Bengkilu village subdistrist, Tujuh Belas of Bengkayang Regency. The data was analysis by social analysis (SNA) with communication network among farmers. The code of network in this research is namely node. The respondents is head of household. The research show the network is like a form like wheel. The higest degree of centrality (ds) is 0,31 that node of 69 from respondents. This higest degree belonged to Pemangku Adat of Laek Hamlet. In this case He has strong links in giving some imfortant information about the rituals adat, prohibition, taboo and customary low (adat low) in slash and burn activity. While the weak degree of centrality is 0,01 with the node of 123 and 159. The weak links is belonged to head of customary sociaty in doing slash and burn or shifting cultivation activity are: (1) The adat rituals in shifting cultivation (2) The adat law. This adat low is as one jars (tempayan), one kampoong chicken. The weigh of chicken with one a high kilogram and also one kilogram yellow rice (tanung perbanyu), all this adat low where paid for the spirit of padi (Nok Naya). (3) sixteen stages of activity in shifting cultivation activity in Laek.Keywords: adat, communication, local wisdom, shifting cultivation, social network.